Power Systems’ Connectivity and Resiliency: Modeling, Simulation and Analysis - Paul Cristian Andrei; Horia Andrei (Energies, 2022)
Over the last decade, online data acquisition and processing of power systems’ parameters led to significant improvements in power systems’ operability, control and reliability [...]